Peran Gereja Dalam Dalam Mendidik Anak-Anak Terlibat Dalam Pelayanan Semenjak Dini - Raden Deddy Kurniawan; Stimson Hutagalung; Rolyana Ferinia (JURNAL KADESI, 2021)
The church has a very important role in providing mentoring services for the children of its congregation members, this must be done from an early age while they can still be shaped as desired. The church is a center for ministry training and this can be done since they were children, there are several forms of service that can be done in childhood such as singing, Bible stories and conveying memorized verses from the Bible. If this is developed then in the future they will be better prepared to be involved in better and wider services. For this reason, the church must provide them with both coaching support, adequate space and opportunities to serve in the church. Through this research, it is hoped that the results will be that parents and the church pay more attention to the children of church members to prepare them for the present and the future. And if this is done they are less likely to leave the church or the truth.